Quality of life following treatment for T1a glottic cancer with surgery or radiotherapy: outcomes from the Head and Neck 5000 cohort. (14th October 2021) - O'Hara, James; Whitmarsh, Alex; Pring, Miranda; Thomas, Steve; Ness, Andy
Abstract: Objectives: To investigate the quality of life in patients treated with either RT or surgery alone for T1a glottic carcinoma. Design: This prospective cohort study aims to assess generic‐ and disease‐specific patient‐reported QoL in patients treated with either surgery or RT for T1a glottic carcinoma. Settings: Multicentre, secondary care specialist head and neck units in the UK. Participants: Participants were recruited as part of the multicentre, prospective Head and Neck 5000 cohort between 2011 and 2014. Main outcome measures: Baseline demographic data were collected. All participants completed the EORTC QLQ C30 and EORTC QLQ H&N35 questionnaires at baseline, 4 months, 12 months and after 36 months. Results: One hundred and twenty three participants received radiotherapy only ( n  = 68) or surgery only ( n  = 55). Overall QoL scores were similar between both groups. The median (IQR) EORTC QLQ C30 summary scores at 12 months were 89.3 (79.1, 95.7) and 92.6 (74.4, 97.9) for the radiotherapy and surgery groups respectively. The equivalent summary scores for the EORTC QLQ H&N35 were 91.9 (83.8, 94.9) and 90.4 (85.5, 94.9). There was a modest difference in some QoL subscales between the groups, but no differences existed beyond 4 months. Conclusions: Patient‐reported QoL is similar following either radiotherapy or surgery for T1a glottic carcinoma. These data support current guidance recommended TLM for this disease.